Principles of international politics : - Bueno de Mesquita, Bruce (CQ Press, 2003)
This self-interest is the decisive motivation for action in the international arena and forms the theoretical backbone for this distinct, exciting departure from other introductory texts. Bruce Bueno de Mesquita has now enhanced and improved this exciting text's coverage and conceptual focus, while revising and updating chapters to make Principles even more accessible to students